Christian neo-orthodox and its religious thought: an analysis - Rahmat, Nur Syahirah; Abdul Rahim, Adibah (IIUM Press, International Islamic University Malaysia, 2017)
The book attempts to examine the approach of Christian neoorthodoxy which claims to occupy a middle position between traditional orthodoxy and liberalism in reconstructing the religious thought of Christianity. The modernity, evidently has brought benefits to mankind, is turned out to be a movement which advocated the idea of emancipation from religion. This idea presented a number of challenges to world religions especially with regard to traditional religious beliefs and practices. However, this book mainly focuses on how Christian neo-orthodoxy responds to those challenges. The study particularly discusses the re-construction of religious thoughts of Christian neo-orthodoxy and its theological issues. The issues that have been touched are, the concept of God, the concept of Sinfulness of man and the concept of scripture. All the theological issues are analysed from the Islamic point of view. The strategy to account for the study of religious thought of Christian neo– orthodoxy on selected theological issues and its analysis from Islamic view is as follows:- Chapter One is an introduction of the study. Chapter Two presented the background of Christian neoorthodoxy which includes the history of the emergence of Christian neo-orthodoxy’s movement and its proponents. Meanwhile, the major theological issues of Christian neoorthodoxy are discussed in Chapter Three. The discussion involves the Christian neo-orthodoxy views on the concept of God, the concept of Sinfulness of man and the concept of scripture. The Islamic perspective on those selected theological issues in Christian neo-orthodoxy is explained in Chapter Four. In Chapter Five, the study concludes that there are significant differences between Christian neo-orthodoxy and Islam in terms of their theological issues. Islam primarily upholds the supremacy of the tradition derived from the Qur’an and Sunnah as the concrete principles in all matters, thoughts and disciplines.